Honeycomb ceramic carrier with controllable pore diameter as well as preparation method and application of honeycomb ceramic carrier

By adjusting the type and proportion of pore-forming agents, a honeycomb ceramic carrier with controllable pore size was prepared, which solved the problem of difficult to achieve the narrow micropore distribution of existing particulate filters, improved filtration efficiency and reduced pressure drop.

CN119462201APending Publication Date: 2025-02-18SHANDONG SINOCERA FUNCTIONAL MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411600207.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing particulate filters are difficult to achieve narrow micropore distribution, resulting in low filtration efficiency and high pressure drop, which cannot meet the strict emission regulations.

Method used

By adjusting the type, particle size and mass percentage of traditional pore-forming agents, a honeycomb ceramic carrier with controllable pore size is prepared to ensure the control of the median pore size of the partition wall and the distribution of narrow pores.

Benefits of technology

The narrow pore distribution of honeycomb ceramic carriers is achieved, filtration efficiency is improved, the system pressure drop is reduced, and strict emission regulations are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005128082700000161
    Figure BDA0005128082700000161
  • Figure BDA0005128082700000171
    Figure BDA0005128082700000171
  • Figure BDA0005128082700000172
    Figure BDA0005128082700000172
Patent Text Reader

Abstract

The invention provides an aperture-controllable honeycomb ceramic carrier and a preparation method and application thereof, and relates to the technical field of catalytic materials.By controlling and removing the influence of inorganic raw materials on the aperture of a honeycomb ceramic compartment, the relation between a pore-forming agent and the median aperture of a honeycomb ceramic target is found, and by controlling the median particle size of the pore-forming agent, the aperture-controllable honeycomb ceramic carrier is obtained. The difference between the median particle size of the pore-forming agent and the maximum median particle size of the inorganic raw material is limited to be higher than 5 microns, the influence of the particle size of the inorganic raw material on the median particle size of the honeycomb ceramic is reduced, and meanwhile, the consistency of the raw materials and the pore-forming agent particles is controlled to be lower than 0.6; the error between the median pore diameter of the prepared honeycomb ceramic and the target median pore diameter is less than 10%, and meanwhile, the honeycomb ceramic has narrower pore diameter distribution (Dflt); and 0.5.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalytic materials, and in particular to a honeycomb ceramic carrier with controllable pore size and a preparation method and application thereof. Background Art

[0002] Particle filters are used to filter fine particulate matter (PM) emitted by gasoline and diesel vehicles. Particle filters have a special honeycomb structure. The structure consists of a honeycomb body separated by porous walls and plugged holes arranged at the air inlet and exhaust ports, and the plugged holes are arranged in a staggered pattern like chess pieces. When the exhaust gas from the engine flows into the inlet of the filter, the tiny particles carried are captured at the plugged holes, while the gas passes through the pore walls of the honeycomb structure into the adjacent compartments and is finally discharged. Depending on the application object, particle filters can be divided into gasoline particulate filters (GPF) for gasoline vehicles and diesel particulate filters (DPF) for diesel vehicles. At present, these honeycomb particle filters usually use mature cordierite ceramics as the filter body material.

[0003] With the introduction of Euro VII emission regulations, there are stricter restrictions on PM and PN. In order to improve filtration efficiency and reduce back pressure, the particulate filter is required to have a higher porosity and narrow pore distribution.

[0004] In filter design, when the median pore size (D50) is kept consistent, the concentration of micropore distribution becomes a key factor affecting performance. Specifically, the more concentrated the micropore distribution is (that is, the narrower the distribution range), the significantly reduced pressure drop caused by it, and the significantly improved filtration efficiency. The fundamental reason for this phenomenon is that the concentration of micropore distribution reduces the number of small pores that are prone to cause additional pressure drop and have limited contribution to particle capture, while also limiting the proportion of large pores that have poor particle filtration effects. This mechanism effectively reduces the overall pressure drop of the system and significantly enhances filtration efficiency. Therefore, achieving a narrow micropore distribution is a crucial technical indicator in filter design.

[0005] CN112430123A uses hollow silica microspheres as pore-forming agents. Low-melting-point talc reacts with hollow silica microspheres to remove the surface shell and release the internal pores, thereby forming narrowly distributed micropores for a particle collector.

[0006] CN113786689A uses quasi-spherical silica as raw material, which has a narrow particle size distribution. It retains a part of the stacking characteristics of the spherical material, forms stacking holes, reduces the amount of pore-forming agent added, and utilizes a narrow particle size distribution to form more uniform stacking holes and promote the formation of narrow distributed micropores of the particle collector.

[0007] It is difficult to achieve narrow pore distribution by adjusting the type, particle size and mass percentage of traditional pore-forming agents with current technology. Therefore, it is very important to develop a honeycomb ceramic carrier that can control the pore size of the next door and achieve narrow pore distribution by adjusting the type, particle size and mass percentage of traditional pore-forming agents. This is conducive to reducing costs and is in line with green and sustainable development.

[0008] In view of this, the present invention is proposed. Summary of the invention

[0009] One of the purposes of the present invention is to provide a honeycomb ceramic carrier with controllable pore size, so as to solve at least one of the technical problems existing in the prior art.

[0010] The second object of the present invention is to provide a method for preparing the above-mentioned honeycomb ceramic carrier with controllable pore size.

[0011] The third object of the present invention is to provide the application of the above-mentioned honeycomb ceramic carrier with controllable pore size.

[0012] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0013] The present invention provides a honeycomb ceramic carrier with controllable pore size, wherein the honeycomb ceramic carrier has a plurality of compartments separated by partition walls; the partition walls are porous structures, and the pores between the compartments are blocked alternately; during gas filtering, the gas flows in from the inlet end of the honeycomb ceramic carrier and flows out from the outlet end of the honeycomb ceramic structure through the porous partition walls.

[0014] The blank includes: inorganic raw materials, pore-forming agent, binder, lubricant and water;

[0015] The inorganic raw materials and pore-forming agent are selected according to the following conditions:

[0016] (1)D M 50 = D50 + k * Dz50;

[0017] (2) The maximum consistency of each inorganic raw material and pore-forming agent is Y < 0.6;

[0018] (3)X=Dz50-D W 50, X>5 μm; and

[0019] (4)D Z 50 Actual value in D Z 50 calculated value within the range of ±1μm;

[0020] Among them, D M 50 is the target median pore size D50 of the honeycomb ceramic structure partition wall;

[0021] D50 is the median pore diameter of the formulation without pore former;

[0022] D Z 50 is the arithmetic median particle size D50 of each pore-forming agent;

[0023] D W 50 is the largest median particle size D50 among all inorganic raw materials;

[0024] K is 0.188.

[0025] The present invention can obtain the particle size of the pore former required by the target honeycomb ceramic by using the median pore size of the target product and the median pore size of the honeycomb ceramic prepared under the same formula without the pore former. And by limiting the pore former, raw material particle size, particle size distribution consistency and pore former material precision, it is possible to prepare the honeycomb ceramic with the target pore size while making its D f =(D 50 -D 10 ) / D 50 <0.5, aperture D f The pore size distribution is narrower.

[0026] Further, the median particle size of each pore former is between 5 and 70 μm, for example, it can be, but not limited to, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm or 70 μm;

[0027] Preferably, the arithmetic median particle size D of each pore-forming agent is Z 50 is 10 to 55 μm, for example, but not limited to 10 μm, 20 μm, 30 μm, 40 μm, 50 μm or 55 μm;

[0028] Preferably, the largest median particle size D of each inorganic raw material is W 50 is 10 to 30 μm, for example, it can be, but not limited to, 10 μm, 20 μm or 30 μm.

[0029] Furthermore, |D M 50-D S 50| / D S 50<10%;

[0030] Among them, D S 50 is the actual median pore size of the honeycomb structure;

[0031] When the inorganic raw materials and pore-forming agents are selected according to the above conditions, the prepared honeycomb ceramic carrier meets the design requirements. M 50-D S 50| / D S 50*100% is less than 10%, and a honeycomb ceramic carrier close to the expected one can be prepared. And its pore size distribution range is narrow, and its D f =(D 50-D 10 ) / D 50 <0.5.

[0032] Preferably, the D S 50 is 5 to 25 μm, for example, it can be, but not limited to, 5 μm, 10 μm, 15 μm, 20 μm or 25 μm.

[0033] Furthermore, the compartments are in a square or rectangular shape; and / or, the compartments are arranged in a checkerboard pattern with holes blocked alternately in the cross section of the honeycomb ceramic carrier.

[0034] Preferably, the pore density of the porous structure is 200-500 cpsi, for example, but not limited to 200 cpsi, 300 cpsi, 400 cpsi or 500 cpsi.

[0035] Preferably, the porosity of the porous structure is greater than 50%.

[0036] The volume of the honeycomb ceramic carrier is not specifically limited. Typically, its height may be 50-200 mm, its diameter may be 80-170 mm, and its partition wall thickness may be 120-300 μm.

[0037] Further, the inorganic component includes at least one of talc, kaolin, calcined kaolin, alumina, aluminum hydroxide and silicon dioxide;

[0038] Preferably, the inorganic raw materials include talc, kaolin, silica, alumina and aluminum hydroxide, which account for 30% to 45% by weight, for example, but not limited to 30%, 35%, 40% or 45%; 5% to 35%, for example, but not limited to 5%, 10%, 15%, 20%, 25%, 30% or 35%; 4% to 25%, for example, but not limited to 4%, 10%, 15%, 20% or 25%; 10% to 25%, for example, but not limited to 10%, 15%, 20% or 25%; 8% to 20%, for example, but not limited to 8%, 10%, 15% or 20%; preferably 38% to 45%, 8% to 30%, 4% to 20%, 8% to 20% and 13% to 18%.

[0039] Preferably, the particle size ranges of the talc, kaolin, silicon dioxide, alumina and aluminum hydroxide are: 5-25 μm, for example, but not limited to 5 μm, 10 μm, 15 μm, 20 μm or 25 μm; 5-12 μm, for example, but not limited to 5 μm, 8 μm, 10 μm or 12 μm; 3-15 μm, for example, but not limited to 3 μm, 5 μm, 10 μm or 15 μm; 1-8 μm, for example, but not limited to 1 μm, 2 μm, 5 μm or 8 μm; 1-8 μm, for example, but not limited to 1 μm, 2 μm, 5 μm or 8 μm. Preferably, 10-23 μm, 6-10 μm, 3-14 μm, 2-7 μm and 1-6 μm.

[0040] Furthermore, the pore-forming agent accounts for 10% to 30% of the total mass of the inorganic raw material, for example, but not limited to 10%, 15%, 20%, 25% or 30%.

[0041] Typical pore-forming agents may be selected from at least one of walnut shell powder, graphite, starch, water-absorbing resin, polymethyl methacrylate, and expanded microspheres;

[0042] Preferably, the binder accounts for 5% to 15% of the total mass of the inorganic raw material, for example, it may be, but is not limited to, 5%, 10% or 15%.

[0043] Typical binders may be selected from at least one of ethylene glycol, hydroxymethyl cellulose, modified cellulose, polyethylene oxide and polyvinyl pyrrolidone.

[0044] Preferably, the lubricant accounts for 1% to 5% of the total mass of the inorganic raw material, for example, it may be, but is not limited to, 1%, 2% or 5%;

[0045] Typical lubricants may be selected from at least one of glycerin, potassium laurate, tall oil and palm oil.

[0046] The present invention also provides a method for preparing the above-mentioned honeycomb ceramic carrier with controllable pore size, comprising the following steps:

[0047] (1) Select inorganic raw materials and pore-forming agents according to conditions;

[0048] (2) dry-mixing the inorganic raw materials, pore-forming agent and binder in the formulated amounts to obtain a mixed powder;

[0049] (3) Lubricant and water are added to the mixed powder to perform wet mixing, kneading, extrusion, drying and cutting to prepare a honeycomb ceramic carrier.

[0050] Furthermore, the dry mixing is performed using a plowshare high-speed mixer; preferably, the dry mixing time is 10 to 30 minutes and the frequency is 10 to 60 Hz;

[0051] Preferably, the wet mixing time is 1 to 20 minutes, and the wet mixing speed is 10 to 60 Hz;

[0052] Preferably, a biaxial kneading machine is used for kneading, and the kneading time is 30 to 180 minutes;

[0053] Preferably, extruding by vacuum mud kneading;

[0054] Preferably, microwave drying is used.

[0055] Furthermore, extrusion is performed using a die having a slit corresponding to the shape of the compartment.

[0056] In addition, the present invention also provides the use of the above-mentioned honeycomb ceramic carrier with controllable pore size or the honeycomb ceramic carrier prepared by the above-mentioned preparation method in the exhaust purification of motor vehicles.

[0057] Compared with the prior art, the present invention has the following beneficial effects:

[0058] The present invention controls and removes the influence of inorganic raw materials on the pore size of honeycomb ceramic compartments, finds the relationship between the pore-forming agent and the target median pore size of honeycomb ceramics, controls the median particle size of the pore-forming agent, and further limits the difference between the median particle size of the pore-forming agent and the maximum median particle size of the inorganic raw materials to be higher than 5 μm, thereby reducing the influence of the particle size of the inorganic raw materials on the median pore size of the honeycomb ceramics. At the same time, the consistency of each raw material and the pore-forming agent particles is controlled to be lower than 0.6, so that the error between the median pore size of the prepared honeycomb ceramic and the target median pore size is lower than 10%, and the honeycomb ceramic has a narrower pore size distribution, and its D f <0.5. DETAILED DESCRIPTION

[0059] Below in conjunction with the embodiments and examples, the present application is further described in detail. These embodiments and examples are only used to illustrate the present application and are not used to limit the scope of the present application. The purpose of providing these embodiments and examples is to make the understanding of the disclosure of the present application more thorough and comprehensive. It should also be understood that the present application can be implemented in many different forms, and is not limited to the embodiments and examples described herein. Those skilled in the art can make various changes or modifications without violating the connotation of the present application, and the equivalent form obtained also falls within the protection scope of the present application. In addition, in the description below, a large number of specific details are given in order to provide a more comprehensive understanding of the present application. It should be understood that the present application can be implemented without one or more of these details.

[0060] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0061] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0062] In this application, the terms "first", "second", etc. in "the first aspect", "the second aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0063] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0064] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical range disclosed in the present application should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows for broadly including quantitative intervals such as percentage intervals, ratio intervals, and ratio intervals.

[0065] All documents mentioned in this application are cited as references in this application, just as each document is cited as reference separately. Unless they conflict with the application purpose and / or technical solution of this application, the cited documents involved in this application are cited with all contents and all purposes. When the cited documents are involved in this application, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also cited. When the cited documents are involved in this application, the examples and preferred methods of the cited relevant technical features can also be incorporated into this application as references, but are limited to the implementation of this application. It should be understood that when the cited content conflicts with the description in this application, the present application shall prevail or be modified adaptively according to the description of this application.

[0066] In this application specification, “D S50" refers to the median pore size of the partition wall of the actually prepared honeycomb ceramic carrier. S The test method for 50" is mercury intrusion method, which is measured by making a sample block with a length, width and height of 10mm*10mm*15mm using a mercury intrusion instrument (MicroActive AutoPore V 9600Version 2.03.00) from Micromeritics. The test method is the national standard: GB / T21650.1-2008.

[0067] In this application specification, “D Z 50" refers to the arithmetic median particle size of various pore-forming agents of the actually prepared honeycomb ceramic carrier. Z 50 = D Z1 *Pore-forming agent 1 ratio + D Z2 *Pore-forming agent 2 proportion +………+D ZN *Pore-forming agent N ratio. "Y" in this application specification refers to the consistency of raw materials or pore-forming agent particles. Z The test method for 50" and Y is to take a small amount of sample and measure it using Malvern Laser Particle Size Analyzer 2000. The test method is GB / T 19077-2016.

[0068] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0069] Example 1

[0070] Talc with a particle size of 11 μm, kaolin with a particle size of 8 μm, silicon dioxide with a particle size of 8 μm, alumina with a particle size of 6 μm, aluminum hydroxide with a particle size of 5 μm, starch pore former with a particle size of 28.2 μm, and graphite pore former with a particle size of 18.9 μm. Add to a plow mixer and dry mix for 20 minutes, the rotation speed is 45 Hz, after the dry mixing, add 1% of the mass fraction of the inorganic raw material lubricant and 40% of the mass fraction of the inorganic raw material water for wet mixing, the wet mixing time is 8 minutes, and the rotation speed is 45 Hz. The obtained raw material mixture is added to a biaxial kneader and kneaded for 25 minutes; after the kneaded mud is smelted, it is put into an extruder and extruded into a blank using a 300 mesh mold with a wall thickness of 8 mil. Subsequently, the above-mentioned honeycomb ceramic carrier is obtained by microwave drying, plugging, and oxidation sintering. Among them, talc, kaolin, silica, alumina and aluminum hydroxide account for 40.1%, 16.0%, 11.3%, 16.5% and 16.1% of the inorganic raw materials, and starch pore formers account for 10% of the total mass of inorganic raw materials and graphite pore formers account for 5%.

[0071] Example 2

[0072] Talc with a particle size of 11 μm, kaolin with a particle size of 8 μm, silicon dioxide with a particle size of 4 μm, alumina with a particle size of 3 μm, aluminum hydroxide with a particle size of 2 μm, starch pore former with a particle size of 27.1 μm, graphite pore former with a particle size of 14.3 μm, and walnut shell powder with a particle size of 13.5 μm. Add to a plow mixer and dry mix for 20 minutes, the rotation speed is 45 Hz, after the dry mixing, add 1% of the mass fraction of the inorganic raw material lubricant and 41% of the mass fraction of the inorganic raw material water for wet mixing, the wet mixing time is 8 minutes, and the rotation speed is 45 Hz. The obtained raw material mixture is added to a biaxial kneader and kneaded for 25 minutes; after the kneaded mud is smelted, it is put into an extruder and extruded into a blank using a 300 mesh mold with a wall thickness of 8 mil. Subsequently, the above-mentioned honeycomb ceramic carrier is obtained by microwave drying, plugging, and oxidation sintering. Among them, talc, kaolin, silica, alumina and aluminum hydroxide account for 40.1%, 16.0%, 11.3%, 16.5% and 16.1% of the inorganic raw materials respectively, and starch pore former accounts for 6.5% of the total mass of inorganic raw materials, graphite pore former accounts for 7.5% and walnut shell powder pore former accounts for 4%.

[0073] Example 3

[0074] Talc with a particle size of 20 μm, kaolin with a particle size of 8 μm, silicon dioxide with a particle size of 12 μm, alumina with a particle size of 5 μm, aluminum hydroxide with a particle size of 5 μm, starch pore former with a particle size of 41 μm, graphite pore former with a particle size of 26.1 μm and walnut shell powder with a particle size of 13.5 μm. Add to a plow mixer and dry mix for 20 minutes, the rotation speed is 45 Hz, after the dry mixing is completed, add 1% of the mass fraction of the inorganic raw material lubricant and 41% of the mass fraction of the inorganic raw material water for wet mixing, the wet mixing time is 8 minutes, and the rotation speed is 45 Hz. The obtained raw material mixture is added to a biaxial kneader and kneaded for 25 minutes; after the kneaded mud is smelted, it is put into an extruder and extruded into a blank using a 300 mesh mold with a wall thickness of 8 mil. Subsequently, the above-mentioned honeycomb ceramic carrier is obtained by microwave drying, plugging, and oxidation sintering. Among them, talc, kaolin, silica, alumina and aluminum hydroxide account for 40.1%, 16.0%, 11.3%, 16.5% and 16.1% of the inorganic raw materials, and starch pore former accounts for 11% of the total mass of inorganic raw materials, graphite pore former accounts for 5% and walnut shell powder pore former accounts for 4%.

[0075] Example 4

[0076] Talc with a particle size of 20 μm, kaolin with a particle size of 8 μm, silicon dioxide with a particle size of 14 μm, alumina with a particle size of 6 μm, aluminum hydroxide with a particle size of 5 μm, PMMA beads with a particle size of 51.1 μm, 39.7 μm starch and 28 μm walnut shell powder. Add to a plow mixer and dry mix for 20 minutes, the rotation speed is 45 Hz, after the dry mixing, add 1% of the mass fraction of the inorganic raw material lubricant and 42% of the mass fraction of the inorganic raw material water for wet mixing, the wet mixing time is 8 minutes, and the rotation speed is 45 Hz. The obtained raw material mixture is added to a biaxial kneader for kneading for 25 minutes; after the kneaded mud is smelted, it is put into an extruder and extruded into a blank using a 300 mesh mold with a wall thickness of 8 mil. Subsequently, the above-mentioned honeycomb ceramic carrier is obtained by microwave drying, plugging, and oxidation sintering. Among them, talc, kaolin, silica, alumina and aluminum hydroxide account for 39.2%, 28.6%, 4.9%, 9.5% and 17.8% of the inorganic raw materials, and PMMA ball pore-forming agent accounts for 12% of the total mass of inorganic raw materials, 8% starch pore-forming agent and 2% walnut shell powder pore-forming agent.

[0077] Example 5

[0078] Talc with a particle size of 15 μm, kaolin with a particle size of 7 μm, silicon dioxide with a particle size of 7 μm, alumina with a particle size of 3 μm, aluminum hydroxide with a particle size of 5 μm, PMMA beads with a particle size of 49.3 μm, 26.9 μm starch and 15 μm walnut shell powder. Add to a plow mixer and dry mix for 20 minutes, the rotation speed is 45 Hz, after the dry mixing, add 1% of the mass fraction of the inorganic raw material lubricant and 42% of the mass fraction of the inorganic raw material water for wet mixing, the wet mixing time is 8 minutes, and the rotation speed is 45 Hz. The obtained raw material mixture is added to a biaxial kneader for kneading for 25 minutes; after the kneaded mud is smelted, it is put into an extruder and extruded into a blank using a 300 mesh mold with a wall thickness of 8 mil. Then, the above-mentioned honeycomb ceramic carrier is obtained by microwave drying, plugging, and oxidation sintering. Among them, talc, kaolin, silica, alumina and aluminum hydroxide account for 39.2%, 28.6%, 4.9%, 9.5% and 17.8% of the inorganic raw materials, and PMMA ball pore-forming agent accounts for 5% of the total mass of inorganic raw materials, starch pore-forming agent accounts for 13.5% and walnut shell powder pore-forming agent accounts for 5%.

[0079] Example 6

[0080] Talc with a particle size of 20 μm, kaolin with a particle size of 7 μm, silicon dioxide with a particle size of 7 μm, alumina with a particle size of 3 μm, aluminum hydroxide with a particle size of 5 μm, PMMA beads with a particle size of 46.8 μm, 31.3 μm starch and 15.1 μm walnut shell powder. Add to a plow mixer and dry mix for 20 minutes, the rotation speed is 45 Hz, after the dry mixing, add 1% of the mass fraction of the inorganic raw material lubricant and 42.5% of the mass fraction of the inorganic raw material water for wet mixing, the wet mixing time is 8 minutes, and the rotation speed is 45 Hz. The obtained raw material mixture is added to a biaxial kneader for kneading for 25 minutes; after the kneaded mud is smelted, it is put into an extruder and extruded into a blank using a 300 mesh mold with a wall thickness of 8 mil. Then, the above-mentioned honeycomb ceramic carrier is obtained by microwave drying, plugging, and oxidation sintering. Among them, talc, kaolin, silica, alumina and aluminum hydroxide account for 39.2%, 28.6%, 4.9%, 9.5% and 17.8% of the inorganic raw materials respectively, and PMMA ball pore-forming agent accounts for 20% of the total mass of inorganic raw materials, 4% starch pore-forming agent and 3% walnut shell powder pore-forming agent.

[0081] Example 7

[0082] Talc with a particle size of 15 μm, kaolin with a particle size of 7 μm, silicon dioxide with a particle size of 4 μm, alumina with a particle size of 3 μm, aluminum hydroxide with a particle size of 5 μm, PMMA beads with a particle size of 52.7 μm, 35 μm starch and 20.7 μm graphite. Add to a plow mixer and dry mix for 20 minutes, the rotation speed is 45 Hz, after the dry mixing, add 1% of the mass fraction of the inorganic raw material lubricant and 43% of the mass fraction of the inorganic raw material water for wet mixing, the wet mixing time is 8 minutes, and the rotation speed is 45 Hz. The obtained raw material mixture is added to a biaxial kneader for kneading for 25 minutes; after the kneaded mud is smelted, it is put into the extruder and extruded into a blank using a 300 mesh mold with a wall thickness of 8 mil. Then, the above-mentioned honeycomb ceramic carrier is obtained by microwave drying, plugging, and oxidation sintering. Among them, talc, kaolin, silica, alumina and aluminum hydroxide account for 40.1%, 23.3%, 8%, 14.4% and 14.2% of the inorganic raw materials, and PMMA bead pore former accounts for 3% of the total mass of inorganic raw materials, starch pore former accounts for 11% and graphite pore former accounts for 16%.

[0083] Example 8

[0084] Talc with a particle size of 20 μm, kaolin with a particle size of 7 μm, silicon dioxide with a particle size of 7 μm, alumina with a particle size of 3 μm, aluminum hydroxide with a particle size of 7 μm, graphite with a particle size of 50.2 μm, 38.9 μm water-absorbing resin and 29.8 μm walnut shell powder. Add to a plow mixer and dry mix for 20 minutes, the rotation speed is 45 Hz, after the dry mixing is completed, add 1% of the mass fraction of the inorganic raw material lubricant and 45% of the mass fraction of the inorganic raw material water for wet mixing, the wet mixing time is 8 minutes, and the rotation speed is 45 Hz. The obtained raw material mixture is added to a biaxial kneader and kneaded for 25 minutes; after the kneaded mud is smelted, it is put into an extruder and extruded into a blank using a 300 mesh mold with a wall thickness of 8 mil. Then, the above-mentioned honeycomb ceramic carrier is obtained by microwave drying, plugging, and oxidation sintering. Among them, talc, kaolin, silica, alumina and aluminum hydroxide account for 40.1%, 23.3%, 8%, 14.4% and 14.2% of the inorganic raw materials respectively, and the total mass of inorganic raw materials includes 5.5% graphite pore former, 2% absorbent resin pore former and 5.5% walnut shell powder pore former.

[0085] Example 9

[0086] Talc with a particle size of 20 μm, kaolin with a particle size of 7 μm, silicon dioxide with a particle size of 7 μm, alumina with a particle size of 3 μm, aluminum hydroxide with a particle size of 5 μm, starch with a particle size of 55.0 μm, 36.4 μm water-absorbing resin and 25.6 μm walnut shell powder. Add to a plow mixer and dry mix for 20 minutes, the rotation speed is 45 Hz, after the dry mixing is completed, add 1% of the mass fraction of the inorganic raw material lubricant and 60% of the mass fraction of the inorganic raw material water for wet mixing, the wet mixing time is 8 minutes, and the rotation speed is 45 Hz. The obtained raw material mixture is added to a biaxial kneader for kneading for 25 minutes; after the kneaded mud is smelted, it is put into an extruder and extruded into a blank using a 300 mesh mold with a wall thickness of 8 mil. Then, the above-mentioned honeycomb ceramic carrier is obtained by microwave drying, plugging, and oxidation sintering. Among them, talc, kaolin, silica, alumina and aluminum hydroxide account for 40.1%, 23.3%, 8%, 14.4% and 14.2% of the inorganic raw materials respectively, and starch pore former accounts for 2.5% of the total mass of inorganic raw materials, water-absorbent resin pore former accounts for 4% and walnut shell powder pore former accounts for 3.5%.

[0087] Example 10

[0088] Talc with a particle size of 20 μm, kaolin with a particle size of 7 μm, silicon dioxide with a particle size of 12 μm, alumina with a particle size of 3 μm, aluminum hydroxide with a particle size of 5 μm, starch with a particle size of 49.4 μm, 45.2 μm water-absorbing resin and 35.5 μm walnut shell powder. Add to a plow mixer and dry mix for 20 minutes, the rotation speed is 45 Hz, after the dry mixing is completed, add 1% of the mass fraction of the inorganic raw material lubricant and 42% of the mass fraction of the inorganic raw material water for wet mixing, the wet mixing time is 8 minutes, and the rotation speed is 45 Hz. The obtained raw material mixture is added to a biaxial kneader and kneaded for 25 minutes; after the kneaded mud is smelted, it is put into an extruder and extruded into a blank using a 300 mesh mold with a wall thickness of 8 mil. Then, the above-mentioned honeycomb ceramic carrier is obtained by microwave drying, plugging, and oxidation sintering. Among them, talc, kaolin, silica, alumina and aluminum hydroxide account for 40.1%, 23.3%, 8%, 14.4% and 14.2% of the inorganic raw materials respectively, and starch pore former accounts for 8.5% of the total mass of inorganic raw materials, PMMA pellet pore former accounts for 11.5% and walnut shell powder pore former accounts for 5%.

[0089] Embodiment 11

[0090] Talc with a particle size of 15 μm, kaolin with a particle size of 7 μm, silicon dioxide with a particle size of 4 μm, alumina with a particle size of 3 μm, aluminum hydroxide with a particle size of 2 μm, starch with a particle size of 39.2 μm, and 24.9 μm expanded microspheres. Add to a plow mixer and dry mix for 20 minutes, the rotation speed is 45 Hz, after the dry mixing, add 1% of the mass fraction of the inorganic raw material lubricant and 40% of the mass fraction of the inorganic raw material water for wet mixing, the wet mixing time is 8 minutes, and the rotation speed is 45 Hz. The obtained raw material mixture is added to a biaxial kneader and kneaded for 25 minutes; after the kneaded mud is smelted, it is put into the extruder and extruded into a blank using a 300 mesh mold with a wall thickness of 8 mil. Subsequently, the above-mentioned honeycomb ceramic carrier is obtained by microwave drying, plugging, and oxidation sintering. Among them, talc, kaolin, silica, alumina and aluminum hydroxide account for 40.1%, 16%, 11.3%, 16.5% and 16.1% of the inorganic raw materials respectively, and starch pore former accounts for 7% of the total mass of inorganic raw materials, and expanded microsphere pore former accounts for 11%.

[0091] Example 12

[0092] Talc with a particle size of 20 μm, kaolin with a particle size of 7 μm, silicon dioxide with a particle size of 4 μm, alumina with a particle size of 3 μm, aluminum hydroxide with a particle size of 2 μm, starch with a particle size of 42.2 μm, and PMMA beads of 25.8 μm. Add to a plowshare mixer and dry mix for 20 minutes at a rotation speed of 45 Hz. After dry mixing, add 1% of the mass fraction of the inorganic raw material lubricant and 42% of the mass fraction of the inorganic raw material water for wet mixing. The wet mixing time is 8 minutes and the rotation speed is 45 Hz. The obtained raw material mixture is added to a biaxial kneader and kneaded for 25 minutes; after the kneaded mud is smelted, it is put into an extruder and extruded into a blank using a 300 mesh mold with a wall thickness of 8 mil. Subsequently, the above-mentioned honeycomb ceramic carrier is obtained by microwave drying, plugging, and oxidation sintering. Among them, talc, kaolin, silica, alumina and aluminum hydroxide account for 40.1%, 16%, 11.3%, 16.5% and 16.1% of the inorganic raw materials respectively, and starch pore former accounts for 5.5% of the total mass of inorganic raw materials, and PMMA ball pore former accounts for 24.5%.

[0093] Comparative Example 1

[0094] Talc with a particle size of 25 μm, kaolin with a particle size of 7 μm, silicon dioxide with a particle size of 12 μm, alumina with a particle size of 5 μm, aluminum hydroxide with a particle size of 7 μm, starch with a particle size of 32.7 μm, and 18.6 μm expanded microspheres. Add to a plowshare mixer and dry mix for 20 minutes, the rotation speed is 45 Hz, after the dry mixing, add 1% of the mass fraction of the inorganic raw material lubricant and 41% of the mass fraction of the inorganic raw material water for wet mixing, the wet mixing time is 8 minutes, and the rotation speed is 45 Hz. The obtained raw material mixture is added to a biaxial kneader and kneaded for 25 minutes; after the kneaded mud is smelted, it is put into an extruder and extruded into a blank using a 300 mesh mold with a wall thickness of 8 mil. Subsequently, the above-mentioned honeycomb ceramic carrier is obtained by microwave drying, plugging, and oxidation sintering. Among them, talc, kaolin, silica, alumina and aluminum hydroxide account for 40.1%, 16%, 11.3%, 16.5% and 16.1% of the inorganic raw materials respectively, and starch pore former accounts for 8% of the total mass of inorganic raw materials, and expanded microsphere pore former accounts for 14%.

[0095] Comparative Example 2

[0096] Talc with a particle size of 25 μm, kaolin with a particle size of 5 μm, silicon dioxide with a particle size of 12 μm, alumina with a particle size of 5 μm, aluminum hydroxide with a particle size of 7 μm, starch with a particle size of 38.7 μm, 27.6 μm expanded microspheres and 16.8 μm water-absorbing resin. Add to a plowshare mixer and dry mix for 20 minutes, the rotation speed is 45 Hz, after the dry mixing is completed, add 1% of the mass fraction of the inorganic raw material lubricant and 55% of the mass fraction of the inorganic raw material water for wet mixing, the wet mixing time is 8 minutes, and the rotation speed is 45 Hz. The obtained raw material mixture is added to a biaxial kneader and kneaded for 25 minutes; after the kneaded mud is smelted, it is put into an extruder and extruded into a blank using a 300 mesh mold with a wall thickness of 8 mil. Then, the above-mentioned honeycomb ceramic carrier is obtained by microwave drying, plugging, and oxidation sintering. Among them, talc, kaolin, silica, alumina and aluminum hydroxide account for 40.1%, 16%, 11.3%, 16.5% and 16.1% of the inorganic raw materials respectively, and the total mass of inorganic raw materials includes 4.5% starch pore former, 6.5% expanded microsphere pore former and 3% absorbent resin pore former.

[0097] Comparative Example 3

[0098] Talc with a particle size of 20 μm, kaolin with a particle size of 7 μm, silicon dioxide with a particle size of 4 μm, alumina with a particle size of 3 μm, aluminum hydroxide with a particle size of 5 μm, starch with a particle size of 48.6 μm, 36.1 μm expanded microspheres and 28.2 μm walnut shell powder. Add to a plow mixer and dry mix for 20 minutes, the rotation speed is 45 Hz, after the dry mixing, add 1% of the mass fraction of the inorganic raw material lubricant and 43% of the mass fraction of the inorganic raw material water for wet mixing, the wet mixing time is 8 minutes, and the rotation speed is 45 Hz. The obtained raw material mixture is added to a biaxial kneader for kneading for 25 minutes; after the kneaded mud is smelted, it is put into an extruder and extruded into a blank using a 300 mesh mold with a wall thickness of 8 mil. Then, the above-mentioned honeycomb ceramic carrier is obtained by microwave drying, plugging, and oxidation sintering. Among them, talc, kaolin, silica, alumina and aluminum hydroxide account for 40.1%, 23.3%, 8%, 14.4% and 14.2% of the inorganic raw materials respectively, and starch pore former accounts for 14% of the total mass of inorganic raw materials, expanded microsphere pore former accounts for 5% and walnut shell powder pore former accounts for 8%.

[0099] Comparative Example 4

[0100] Talc with a particle size of 20 μm, kaolin with a particle size of 7 μm, silicon dioxide with a particle size of 12 μm, alumina with a particle size of 3 μm, aluminum hydroxide with a particle size of 5 μm, starch with a particle size of 51.8 μm, 31.1 μm expanded microspheres and 9.4 μm PMMA beads. Add to a plow mixer and dry mix for 20 minutes, the rotation speed is 45 Hz, after the dry mixing, add 1% of the mass fraction of the inorganic raw material lubricant and 42% of the mass fraction of the inorganic raw material water for wet mixing, the wet mixing time is 8 minutes, and the rotation speed is 45 Hz. The obtained raw material mixture is added to a biaxial kneader for kneading for 25 minutes; after the kneaded mud is smelted, it is put into the extruder and extruded into a blank using a 300 mesh mold with a wall thickness of 8 mil. Then, the above-mentioned honeycomb ceramic carrier is obtained by microwave drying, plugging, and oxidation sintering. Among them, talc, kaolin, silica, alumina and aluminum hydroxide account for 40.1%, 23.3%, 8%, 14.4% and 14.2% of the inorganic raw materials respectively, and the total mass of inorganic raw materials includes 6% starch pore former, 9% expanded microsphere pore former and 5% PMMA small ball pore former.

[0101] Comparative Example 5

[0102] Talc with a particle size of 15 μm, kaolin with a particle size of 9 μm, silicon dioxide with a particle size of 14 μm, alumina with a particle size of 5 μm, aluminum hydroxide with a particle size of 5 μm, starch with a particle size of 41.5 μm, 22.1 μm water-absorbing resin and 16.5 μm PMMA beads. Add to a plowshare mixer and dry mix for 20 minutes, the rotation speed is 45 Hz, after the dry mixing is completed, add 1% of the mass fraction of the inorganic raw material lubricant and 50% of the mass fraction of the inorganic raw material water for wet mixing, the wet mixing time is 8 minutes, and the rotation speed is 45 Hz. The obtained raw material mixture is added to a biaxial kneader for kneading for 25 minutes; after the kneaded mud is smelted, it is put into an extruder and extruded into a blank using a 300 mesh mold with a wall thickness of 8 mil. Then, the above-mentioned honeycomb ceramic carrier is obtained by microwave drying, plugging, and oxidation sintering. Among them, talc, kaolin, silica, alumina and aluminum hydroxide account for 39.2%, 15.6%, 11.3%, 11.8% and 22.1% of the inorganic raw materials respectively, and starch pore formers account for 13% of the total mass of inorganic raw materials, water-absorbent resin pore formers account for 2% and PMMA ball pore formers account for 3%.

[0103] Comparative Example 6

[0104] Talc with a particle size of 20 μm, kaolin with a particle size of 7 μm, silicon dioxide with a particle size of 12 μm, alumina with a particle size of 3 μm, aluminum hydroxide with a particle size of 5 μm, graphite with a particle size of 52 μm, 32.4 μm water-absorbing resin and 18.9 μm starch. Add to a plow mixer and dry mix for 20 minutes, the rotation speed is 45 Hz, after the dry mixing, add 1% of the mass fraction of the inorganic raw material lubricant and 58% of the mass fraction of the inorganic raw material water for wet mixing, the wet mixing time is 8 minutes, and the rotation speed is 45 Hz. The obtained raw material mixture is added to a biaxial kneader for kneading for 25 minutes; after the kneaded mud is smelted, it is put into the extruder and extruded into a blank using a 300 mesh mold with a wall thickness of 8 mil. Then, the above-mentioned honeycomb ceramic carrier is obtained by microwave drying, plugging, and oxidation sintering. Among them, talc, kaolin, silica, alumina and aluminum hydroxide account for 39.2%, 15.6%, 11.3%, 11.8% and 22.1% of the inorganic raw materials respectively, and the total mass of inorganic raw materials includes 5% graphite pore former, 3.5% absorbent resin pore former and 1.5% starch pore former.

[0105] Table 1

[0106]

[0107]

[0108] Table 2

[0109]

[0110]

[0111] It can be seen from Table 1 and Table 2 that in Examples 1 to 12 of the present invention, when the inorganic raw materials and pore-forming agents in the preparation process meet the following four conditions,

[0112] (1)D M 50 = D50 + k * Dz50;

[0113] (2) The maximum consistency Y of each inorganic raw material and pore-forming agent is less than 0.6;

[0114] (3) X = D Z 50-D W 50, X>5 μm; and

[0115] (4)D Z 50 Actual value in D Z 50 calculated value within the range of ±1μm;

[0116] That is to say, the honeycomb ceramic carrier with controllable pore size that can be used as a filter in the present invention meets the design requirements. M 50-DS 50| / D S 50*100% is less than 10%, and a honeycomb ceramic carrier close to the expected one can be prepared. And its pore size distribution range is narrow, and its D f =(D 50 -D 10 ) / D 50 <0.5.

[0117] D of Comparative Example 1 and Comparative Example 2 Z 50-D W 50<5μm, that is, the difference between the arithmetic median particle size of all pore-forming agents and the median particle size of the largest inorganic raw material is less than 5μm, so that the inorganic raw material has a greater influence on the pore size. M 50-D S 50| / D S 50*100%>10%. D of Comparative Example 3 and Comparative Example 5 Z Actual value and D Z The difference between the theoretical values ​​is greater than 1 μm, which also causes a certain deviation between the D50 of the obtained product and the target, but the deviation is smaller than that of Comparative Examples 1 and 2. The maximum consistency Y of the inorganic raw materials and the pore-forming agents of Comparative Examples 4 and 6 is higher than 0.6, which makes the pore size distribution range wider, and its D f =(D 50 -D 10 ) / D 50 >0.5.

[0118] Therefore, the present invention is very important for the honeycomb ceramic carrier which can control the pore size of the partition wall and achieve narrow pore distribution by adjusting the type, particle size and mass percentage of the traditional pore-forming agent during the preparation process.

[0119] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A honeycomb ceramic carrier with controllable pore size, characterized in that: The honeycomb ceramic substrate has a plurality of compartments separated by partition walls; The partition wall is a porous structure, and the pores between the compartments are blocked alternately; the blank comprises: inorganic raw materials, pore-forming agent, binder, lubricant and water; The inorganic raw materials and pore-forming agent are selected according to the following conditions: (1)D M 50=D50+k*Dz50; (2) The maximum consistency Y among all inorganic raw materials and pore-forming agents is less than 0.6; (3) X = D Z 50-D W 50, X>5 μm; and (4)D Z 50 Actual value in D Z 50 calculated value within the range of ±1μm; Among them, D M 50 is the target median pore size D50 of the honeycomb ceramic structure partition wall; D50 is the median pore diameter of the formulation without pore former; D Z 50 is the arithmetic median particle size D50 of each pore-forming agent; D W 50 is the largest median particle size D50 among all inorganic raw materials; K is 0.

188.

2. The honeycomb ceramic carrier with controllable pore size according to claim 1, characterized in that: The median particle size of each pore former is between 5 and 70 μm; Preferably, the arithmetic median particle size D of each pore-forming agent is Z 50 is 10-55 μm; Preferably, the largest median particle size D of each inorganic raw material is W 50 is 10~30μm.

3. The honeycomb ceramic carrier with controllable pore size according to claim 1, characterized in that: |D M 50-D S 50| / D S 50<10%; Among them, D S 50 is the actual median pore size of the honeycomb structure; Preferably, the D S 50 is 5~25μm.

4. The honeycomb ceramic carrier with controllable pore size according to claim 1, characterized in that: The compartments are in a square or rectangular shape; and / or the compartments are arranged in a checkerboard pattern with holes blocked alternately in the cross section of the honeycomb ceramic carrier; Preferably, the pore density of the porous structure is 200-500 cpsi; Preferably, the porosity of the porous structure is greater than 50%.

5. The honeycomb ceramic carrier with controllable pore size according to any one of claims 1 to 4, characterized in that: The inorganic component comprises at least one of talc, kaolin, calcined kaolin, alumina, aluminum hydroxide and silicon dioxide; Preferably, the inorganic raw materials include talc, kaolin, silicon dioxide, alumina and aluminum hydroxide, which account for 30% to 45%, 5% to 35%, 4% to 25%, 10% to 25% and 8% to 20% respectively based on 100% by weight; preferably 38% to 45%, 8% to 30%, 4% to 20%, 8% to 20% and 13% to 18%; Preferably, the particle size ranges of the talc, kaolin, silica, alumina and aluminum hydroxide are 5-25 μm, 5-12 μm, 3-15 μm, 1-8 μm and 1-8 μm, respectively, and preferably 10-23 μm, 6-10 μm, 3-14 μm, 2-7 μm and 1-6 μm.

6. The honeycomb ceramic carrier with controllable pore size according to any one of claims 1 to 4, characterized in that: The pore-forming agent accounts for 10% to 30% of the total mass of the inorganic raw materials; Preferably, the pore-forming agent comprises at least one of walnut shell powder, graphite, starch, water-absorbing resin, polymethyl methacrylate and expanded microspheres; Preferably, the binder accounts for 5% to 15% of the total mass of the inorganic raw material; Preferably, the binder comprises at least one of ethylene glycol, hydroxymethyl cellulose, modified cellulose, polyethylene oxide and polyvinyl pyrrolidone; Preferably, the lubricant accounts for 1% to 5% of the total mass of the inorganic raw material; Preferably, the lubricant comprises at least one of glycerin, potassium laurate, tall oil and palm oil.

7. The method for preparing a honeycomb ceramic carrier with controllable pore size according to any one of claims 1 to 6, characterized in that: The steps include: (1) Select inorganic raw materials and pore-forming agents according to conditions; (2) dry-mixing the inorganic raw materials, pore-forming agent and binder in the formulated amounts to obtain a mixed powder; (3) Lubricant and water are added to the mixed powder to perform wet mixing, kneading, extrusion, drying and cutting to prepare a honeycomb ceramic carrier.

8. The preparation method according to claim 7, characterized in that: The dry mixing is performed using a plowshare high-speed mixer; preferably, the dry mixing time is 10 to 30 minutes and the frequency is 10 to 60 Hz; Preferably, the wet mixing time is 1 to 20 minutes, and the wet mixing speed is 10 to 60 Hz; Preferably, a biaxial kneading machine is used for kneading, and the kneading time is 30 to 180 minutes; Preferably, extruding by vacuum mud kneading; Preferably, microwave drying is used.

9. The preparation method according to claim 7 or 8, characterized in that: Extrusion is performed using a die having slots corresponding to the shape of the compartments.

10. Use of the honeycomb ceramic carrier with controllable pore size as claimed in any one of claims 1 to 6 or the honeycomb ceramic carrier prepared by the preparation method as claimed in any one of claims 7 to 9 in exhaust purification of motor vehicles.

Citation Information

Patent Citations

  • Narrow-pore-size-distribution and large-size cordierite gasoline particle filter and preparation method thereof

    CN112430123A

  • Cordierite honeycomb ceramic filter with narrow micropore distribution as well as preparation method and application of cordierite honeycomb ceramic filter

    CN113786689A